Original paperThe incidence of fat necrosis in balloon-based breast brachytherapy - Paryani, Nitesh N.; Vallow, Laura; Magalhaes, Wilza; Heckman, Michael G.; Kim, Siyong; Smith, Ashley; Diehl, Nancy N.; McLaughlin, Sarah (Journal of Contemporary Brachytherapy, 2015)
Purpose: To investigate the incidence of and potential risk factors for fat necrosis in high dose-rate (HDR) balloon- based breast brachytherapy (BBB). Material and methods : Fifty-four patients were treated postoperatively with HDR-BBB between May 2007 and December 2010. Median age was 71 years (range: 50-88 years). Median tumor size was 1 cm (range: 0.1-2.7 cm). Forty-four had invasive histology; 43% were grade 1, 24% grade 2, and 15% grade 3. The median margin size was 0.7 cm (range: 0.1-1.5 cm). Results: With a median follow-up of 2.9 years (range: 0.5-5.2 years), local control was 98% with one in-breast failure, and overall survival was 89%. Fifty percent of patients experienced fat necrosis. Seven patients were symptomatic, with the remainder detected by mammography alone. Two patients required surgical resection with pathology confirming fat necrosis; 1 required i.v. steroids. At 1, 3, and 5 years following treatment, estimated cumulative incidences of fat necrosis were 7.5%, 52.7%, and 60.6%. Breast laterality, location, tumor size, histology, margin size, balloon volume, skin distance, skin dose, and number of dwell positions were not significantly associated with fat necrosis on univariate analysis. Conclusions : In this retrospective review of HDR-BBB, we found a 50% incidence of both asymptomatic and symptomatic fat necrosis. Only three patients, however, required intervention. None of the risk factors considered were significantly associated with fat necrosis. Further studies evaluating factors associated with fat necrosis for patients undergoing HDR-BBB are necessary to appropriately assess the risks associated with treatment.